Penerapan Teknik Imajinasi Terbimbing Untuk Mengurangi Nyeri Kepala Pada Pasien Hipertensi Di Rumah Sakit Daerah Kota Lubuklinggau - Nadi Aprilyadi; Jhon Feri; Lestari Ayu (Journal of Complementary in Health, 2021)
Background: Hypertension is an increase in blood pressure from arteries that is systemic or persists in a long period of time. Hypertension can cause headaches. Guided imagination therapy is a technique of using individual imagination that specifically aims to achieve control in relaxation, relaxation can have a direct effect on body functions, the effect of relaxation is to reduce pain in hypertension. The Purpose: this is to determine the reduction of the headache scale in hypertensive patients. before and after the Guided Imagination Technique was applied to the feet to reduce headaches in the Al-Ikhlas room of the Siti Aisyah Hospital, Lubuklinggau City. Research Metods: This is a descriptive study using a case study approach. The subjects in this study were 2 adults with a diagnosis of hypertension. The treatment is carried out directly with the initial assessment of the headache patient and then the intervention of the Guided Imagination Technique to reduce headache pain. The results: it is known that after nursing interventions for 3 consecutive days there is a decrease in the pain scale from the healing time using other drugs. It is hoped that health service institutions can improve the quality of nursing care that focuses on hypertensive patients who experience headaches with the application of Guided Imagination Techniques so that the Guided Imagination Technique intervention SOP can be developed again.